A novel aggregation approach to reduce complexity of system. (19th March 2020) - Naqvi, Sadaf; Nasiruddin, Ibraheem; Ali, Sana
This paper presents a novel approach to reduce the complexity of the system. In every field of engineering, the analysis and synthesis of the system is an important step. While analysing the system, mathematical modelling is the first step. In actual practice the system model is too complicated to analyse, therefore, model order reduction techniques are applied to analyse such a system. In the present work, an exhaustive study is carried out to design reduced order models for a complex system. Conventional techniques are discussed and applied to two area interconnected power system. A method is proposed and applied to multi-area power system. Dynamic responses of original and reduced models have been compared. Results show that the reduced order model is a good representation of the original higher order model.